2022
DOI: 10.3390/cancers14133142
|View full text |Cite
|
Sign up to set email alerts
|

Radon and Lung Cancer: Current Trends and Future Perspectives

Abstract: Lung cancer is a public health problem and the first cause of cancer death worldwide. Radon is a radioactive gas that tends to accumulate inside homes, and it is the second lung cancer risk factor after smoking, and the first one in non-smokers. In Europe, there are several radon-prone areas, and although the 2013/59 EURATOM directive is aimed to regulate indoor radon exposition, regulating measures can vary between countries. Radon emits alpha-ionizing radiation that has been linked to a wide variety of cytot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 81 publications
(118 reference statements)
0
30
0
Order By: Relevance
“…Lung cancer is the most prevalent malignancy in Chinese population, among whose histological subtypes, lung adenocarcinoma (LUAD) accounts for 40% of all lung cancer cases (1)(2)(3). The pathological diagnosis divides lung adenocarcinoma into atypical adenomatous hyperplasia (AAH), adenocarcinoma in situ (AIS), minimally invasive adenocarcinoma (MIA), invasive adenocarcinoma (IAC), in which the former two are non-invasive and the latter two are invasive (4).…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is the most prevalent malignancy in Chinese population, among whose histological subtypes, lung adenocarcinoma (LUAD) accounts for 40% of all lung cancer cases (1)(2)(3). The pathological diagnosis divides lung adenocarcinoma into atypical adenomatous hyperplasia (AAH), adenocarcinoma in situ (AIS), minimally invasive adenocarcinoma (MIA), invasive adenocarcinoma (IAC), in which the former two are non-invasive and the latter two are invasive (4).…”
Section: Introductionmentioning
confidence: 99%
“…B[a]P is a polycyclic aromatic hydrocarbon (PAH) that is a recognized as a class I carcinogen that is present in tobacco, industrial exhaust, and environmental contamination. Additionally, arsenic [ 151 ], radon [ 152 ] and others environmental factors are etiologically related to lung cancer. For instance, it is known that tobacco smoking and second-hand smoke are etiologically related to 70–90% of lung cancer cases worldwide, though this percentage varies depending on the histological type and the sociodemographic factors that are involved [ 153 , 154 ].…”
Section: Hr-hpv-mediated Lung Carcinogenesis: Potential Mechanismsmentioning
confidence: 99%
“…Mining-related lung cancer was first described by Harting Hesse in 1879 [ 8 ]. Since then, much work has been done, and an extensive account of the history of radon, lung cancer, and epidemiological studies can be found elsewhere [ 9 , 10 , 11 ]. In Poland, there are many underground tourist routes in mines and caves, which is why research was conducted on this subject [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%